Модель аналізу стійкості інвестиційних процесів на прикладі інноваційного стартап-проєкту - Сергієнко, Олена Андріанівна; Самусь, Павло Олегович; Соснов, Ігор Ігорович (ТОВ "ДКС Центр", 2024)
У статті досліджено сутність категорії стійкості інвестиційного проєкту в умовах невизначеності зовнішнього середовища. Забезпечення стійкості інвестиційних проєктів є критично важливим завданням в умовах високої невизначеності та мінливості зовнішнього середовища. Здатність проєкту протистояти негативним впливам, адаптуватися до змін та досягати поставлених цілей визначає його успіх та ефективність інвестицій. В наукових працях як вітчизняних, так і зарубіжних фахівців висвітлюються різні аспекти забезпечення стійкості інвестиційних проєктів, зокрема, вплив факторів зовнішнього середовища, методи оцінки ризиків, застосування адаптивних підходів в управлінні проєктами. Проте, питання комплексної оцінки стійкості з урахуванням невизначеності зовнішніх умов потребує подальшого вивчення. Мета даної роботи полягає в узагальненні теоретичних підходів та розробці практичних рекомендацій щодо аналізу і забезпечення стійкості інвестиційних проєктів в нестабільних умовах зовнішнього середовища. Для досягнення поставленої мети передбачається виконання таких завдань: проаналізувати вплив факторів невизначеності зовнішнього середовища на інвестиційні проєкти, розглянути методичні підходи до оцінки стійкості проєктів, сформувати рекомендації щодо вибору стратегій та інструментів забезпечення стійкості на різних етапах реалізації проєктів.

The article examines methods for assessing the sustainability of investment projects, particularly in the face of uncertainty in the external environment. Volatility in economic, political, legal and other external factors creates risks that can negatively impact project goals, costs and timelines. Ensuring project sustainability is thus critically important for successful implementation and return on investment. The research investigates theoretical approaches to defining and evaluating investment project sustainability while considering external uncertainty impacts. It analyzes existing qualitative and quantitative assessment methods, including application of control theory techniques like the Nyquist, Mikhailov and Routh-Hurwitz criteria. These frequency response methods allow modeling a project's transfer function to identify potential instabilities, volatility and deviations from desired performance due to disturbances. The analysis highlights how building an accurate model of the project's dynamics and studying its stability characteristics can reveal vulnerabilities to external shocks before they manifest. For investment projects like startups operating in highly dynamic and unpredictable environments, such sustainability analysis is crucial. It enables project managers to evaluate inherent risks, detect vulnerabilities, and implement adaptive strategies to increase resilience against disruptions. Investors can also use these analytical approaches to make more informed decisions about a project's viability and robustness before committing capital. With insights from sustainability modeling, both project leaders and investors can take preemptive actions to fortify the project against potential deviations from the planned trajectory. The paper provides practical recommendations on selecting appropriate sustainability assessment methods and tools based on the project's characteristics, industry factors and the degree of external uncertainty. Emphasizing adaptive management approaches, the findings offer a framework to enhance the stability and success rate of investment projects amid external volatility. Real-world applications demonstrate how systematic sustainability analysis allows proactive risk mitigation, agile adaptation to changes, and ultimately higher chances of achieving the desired investment outcomes despite environmental turbulence.
Sustainability analysis model for investment processes: a case study of an innovative startup project
Keywords: стійкість; інвестиційний проєкт; невизначеність; зовнішнє середовище; ризики; sustainability; investment project; uncertainty; external environment; risks